A Unified Framework for Theoretical and Experimental Evaluation of Classical and Modern Sorting Algorithms in Real-Time Systems - Wiredu, Japheth Kodua; Akobre, Stephen; Aabaah, Iven; Wumpini, Umar Adam (Journal of Information Systems and Informatics, 2025)
This paper presents a theoretical and experimental evaluation of eight popular sorting algorithms HeapSort, QuickSort, MergeSort, Parallel MergeSort, TimSort, IntroSort, Bitonic Sort, and MSD Radix Sort—assessing their suitability for real-time computing environments. The study combines algorithmic analysis with large-scale benchmarks across various input distributions (random, almost sorted, reverse-sorted) and data scales, focusing on execution time and memory usage. Results show that hybrid and adaptive algorithms outperform classical ones. TimSort had the shortest execution times (as low as 1.0 ms on sorted data), and IntroSort showed consistent performance across data types (11-13 ms on random inputs) with minimal memory (
Keywords: Sorting algorithms, Real-time systems, Hybrid algorithms, Performance evaluation